2013
DOI: 10.1148/radiology.13122829
|View full text |Cite
|
Sign up to set email alerts
|

Probably Benign Lesions at Screening Breast US in a Population with Elevated Risk: Prevalence and Rate of Malignancy in the ACRIN 6666 Trial

Abstract: To prospectively validate predefined breast ultrasonographic (US) Breast Imaging Reporting and Data System (BI-RADS) category 3 criteria in a multicenter setting in an elevated-risk population. Materials and Methods: The American College of Radiology Imaging Network 6666 database was reviewed for prospectively defined BI-RADS category 3 lesions. Patient characteristics, lesion US features at initial detection, and work-up recommendations were analyzed with descriptive statistics. Exact 95% confidence intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 56 publications
5
38
0
1
Order By: Relevance
“…Nevertheless, malignancy is eventually diagnosed in about 3% of these lesions, resulting in a delayed diagnosis of cancer in a considerable number of patients (Sadigh et al 2012a). On the other hand, a recent prospective study evaluating screening ultrasonography reported a BI-RADS 3 category in about 20% of patients, and 16.6% were ultimately sampled for biopsy with a low malignancy rate of 0.8% (Barr et al 2013). BI-RADS 4 lesions have a low to moderate probability of cancer (3%-94%) and biopsy/fine-needle aspiration cytology (FNAC) should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, malignancy is eventually diagnosed in about 3% of these lesions, resulting in a delayed diagnosis of cancer in a considerable number of patients (Sadigh et al 2012a). On the other hand, a recent prospective study evaluating screening ultrasonography reported a BI-RADS 3 category in about 20% of patients, and 16.6% were ultimately sampled for biopsy with a low malignancy rate of 0.8% (Barr et al 2013). BI-RADS 4 lesions have a low to moderate probability of cancer (3%-94%) and biopsy/fine-needle aspiration cytology (FNAC) should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Iso echoic cancers can be difficult to distinguish from fat lobules, particularly in the absence of echogenic rim or effects on surrounding tissue, and may be overrepresented among false negative cancers on US. (64), and including isolated circumscribed benign-appearing masses and probable fat necrosis (Fig 4), with 0.8% (six of 745) of such BI-RADS category 3 lesions malignant in ACRIN 6666 (64). Across four other series, a 0.7 malignancy rate (10 of 1337) has been observed for nonpalpable BI-RADS category 3 lesions seen on US scans (in conjunction with mammography) (65)(66)(67)(68).…”
Section: Technique and Documentationmentioning
confidence: 93%
“…Across four other series, a 0.7 malignancy rate (10 of 1337) has been observed for nonpalpable BI-RADS category 3 lesions seen on US scans (in conjunction with mammography) (65)(66)(67)(68). In the ACRIN 6666 protocol, only one malignancy was identified among BI-RADS 3 lesions because of suspicious changes at 6-month follow-up, and all of the cancers identified because of change at 12 months or less were node negative (64). Because BI-RADS category 3 findings are common on screening US (up to 20% of women) and the malignancy Figure 3 rate is less than 1%, 12-month follow-up may be reasonable, and such findings certainly should not undergo initial biopsy.…”
Section: Technique and Documentationmentioning
confidence: 97%
“…Nodes were classified as malignant or benign by imaging-pathology gold standards: 27 lymph nodes underwent pre-operative fine-needle aspiration; 68 underwent sentinel lymph node biopsy; 5 patients were subjected to axillary lymph node dissection; and 5 lymph nodes with normal images without biopsy had a long-term (minimum of 3 y) imaging clinical follow-up. Although there are no clinical standards for lymph node classification and long-term follow-up, the American College of Radiology (ACR) recommends long-term follow-up in intervals of 6, 12 and 24 mo for breast lesions classified as probably benign, BI-RADS (Breast Imaging and Reporting Data System) 3 (Barr et al 2013).…”
Section: Surgical-pathology Datamentioning
confidence: 99%